Traceview a trace visualization tool - Malony, Allen; Hammerslag, David; Jablonowski, David (1991)
Abstract: "Although incorporating significant performance detail, the generation of large trace files poses problems for performance interpretation. The potential need to compare multiple traces, possibly produced by different means (e.g., measured execution or simulation), exacerbates the difficulties in building general trace analysis and display solutions. This paper describes a trace visualization tool, TRACEVIEW, that provides a convenient, general purpose environment for trace manipulation and display. TRACEVIEW manages trace visualization sessions that the user constructs, handling functions such as trace file I/O, view specification, and display selection
Keywords: Performance; Visualization